2018
DOI: 10.1097/meg.0000000000001030
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban-induced hepatotoxicity: review of the literature and report of new cases

Abstract: Direct-acting oral anticoagulants have been commonly prescribed, even if safety issues regarding the use of these drugs are still an ongoing concern, especially in patients experiencing chronic liver disease. Dedicated postauthorization safety studies should be undertaken to better define rivaroxaban-induced drug-induced liver injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 28 publications
1
23
0
2
Order By: Relevance
“…NOACs are also metabolized by the liver enzyme CYP450 3A and may sometimes produce symptoms which result in elevated enzymes in patients. This question arose because ximelagatran showed hepatotoxic symptoms in its initial stages while the currently used NOACs found no hepatic risk [1,8]. Although NOACs induced hepatotoxicity is unusual, it has evidence of drug-induced liver injury as well as elevated enzyme levels of the liver [8].…”
Section: Hepatotoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…NOACs are also metabolized by the liver enzyme CYP450 3A and may sometimes produce symptoms which result in elevated enzymes in patients. This question arose because ximelagatran showed hepatotoxic symptoms in its initial stages while the currently used NOACs found no hepatic risk [1,8]. Although NOACs induced hepatotoxicity is unusual, it has evidence of drug-induced liver injury as well as elevated enzyme levels of the liver [8].…”
Section: Hepatotoxicitymentioning
confidence: 99%
“…This question arose because ximelagatran showed hepatotoxic symptoms in its initial stages while the currently used NOACs found no hepatic risk [1,8]. Although NOACs induced hepatotoxicity is unusual, it has evidence of drug-induced liver injury as well as elevated enzyme levels of the liver [8]. There is a little more evidence which suggested that NOACs cannot be used in hepatic impairment [27].…”
Section: Hepatotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…После этого были также исключены статьи, в которых не приводятся описания конкретных клинических случаев, итого -в обзор включено 14 статей (рис. 1) [14,15,[17][18][19][20][21][22][23][25][26][27][28][29].…”
Section: материал и методыunclassified
“…Следует обратить внимание, что практически во всех случаях развития гепатотоксичности купирование лабораторных симптомов происходило после отмены ривароксабана, без применения дополнительной терапии. Нормализация лабораторных показателей и купирование клинических проявлений обычно происходило через неделю после отмены ЛС [18][19][20][21]. Возможные механизмы вызванной ривароксабаном гепатотоксичности неизвестны и, вероятно, включают сложные взаимодействия нескольких редких факторов и иммунно-опосредованных реакций.…”
Section: результатыunclassified